?EFFECT OF DIFFERENT HARVESTING TIMES ON THE CORM YIELD OF SOME GLADIOLUS (GLADIOLUS L.)CULTIVARS (Biological Sciences - PJSIR, 1998)
The effects ofthree different harvesting times (when the leaves were green, beginning to yellow and drying) on.the yield of corm and corm lets of commercial Gladiolus varieties; Nova Lux, Mascani, White Prosperity and Piricilla were de- termined in pots under field conditions. The experiment was laid out in split-plot design taking 216 corms of Gladiolus, each with girth of 8-11 cm. The studied parameters relating to new corms were: number of corms, number of cormlets, corm girth (em), cormlet diameter (em), corm weight (g) and cormlet weight (g). The second and third harvesting times gave maximum number of cormlets. The largest girth and the maximum weight of corm were found in the c.v. 'Mascani'. The largest cormlet diameter and corm let weight were obtained from the first harvest.